Estratégia educativa sobre gerenciamento de antimicrobianos – antimicrobial stewardship - para graduandos em enfermagem - Perinoti, Lívia Cristina Scalon da Costa (2023)
Among the measures aimed at minimizing antimicrobial resistance, a problem that was even more exacerbated after the start of the coronavirus (SARS-CoV-2) pandemic, is the Antimicrobial Stewardship Program (ASP). The ASP involves a set of actions aimed at the rational use of antimicrobials in health services. These actions must be carried out by an interprofessional team, including the nurse, a professional who still has an incipient participation in these programs. Expanding the knowledge of future nurses on the subject is essential to increase their participation in the ASP. The use of active methodologies, with the support of Information and Communication Technologies (ICTs) has been shown to be efficient in similar studies. The objective of this study, therefore, was to evaluate the effect of an educational intervention on the ASP - Antimicrobial Stewardship Program, - for undergraduate nursing students. This is a multiple study, carried out in three stages: development and validation by appearance and content by expert judges of the educational strategy; realization of the educational intervention and analysis of knowledge gain; and evaluating its feasibility. In the statistical analysis, absolute frequencies, percentages, measurement, McNemar test, binomial regression models with identity link function, with a significance level of 5% were used. The educational strategy was developed and later validated by 10 expert judges, with a total content validity index greater than 0.90 for appearance and content. The intervention, which consisted of a free course offered on the Portal de Cursos Abertos (PoCA), consisting of 4 domains using the WebQuest methodology, was carried out with 73 nursing students from a college in the interior of the State of São Paulo, being measured the level of knowledge (rate of correct answers) before and after the educational intervention. A better performance was found in the post-test, especially in domain 2, diagnosis of infection and use of antimicrobials, and in domain 3, clinical practice of nurses (p=<0.01). As for practicality, the intervention was considered easy to understand and carry out, and the participants expressed interest in using this type of educational strategy again. The open course without tutoring was developed, validated, applied and evaluated and is a useful tool and is available free of charge to contribute to the training of future nurses in the theme of PGA. Actions aimed at improving the knowledge and awareness of health professionals, in particular nurses, about PGA is one of the ways to contribute to the reduction of antimicrobial resistance in the world.